2021
DOI: 10.1371/journal.ppat.1009195
|View full text |Cite
|
Sign up to set email alerts
|

K18-hACE2 mice develop respiratory disease resembling severe COVID-19

Abstract: SARS-CoV-2 emerged in late 2019 and resulted in the ongoing COVID-19 pandemic. Several animal models have been rapidly developed that recapitulate the asymptomatic to moderate disease spectrum. Now, there is a direct need for additional small animal models to study the pathogenesis of severe COVID-19 and for fast-tracked medical countermeasure development. Here, we show that transgenic mice expressing the human SARS-CoV-2 receptor (angiotensin-converting enzyme 2 [hACE2]) under a cytokeratin 18 promoter (K18) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
229
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(273 citation statements)
references
References 53 publications
(83 reference statements)
30
229
4
Order By: Relevance
“…With the higher infectious dose (10 4 PFU) or with IAV pre-infection, we observed widespread extensive viral antigen expression and involvement of the spinal cord. This suggests some dose dependence of virus spread in the CNS, as it was suspected in another study (Yinda et al, 2021), and an effect of prior damage in the respiratory tract (Clark et al, 2021). At the same time, we and others found virus in the olfactory epithelium and in neurons in the olfactory bulb (Carossino et al, 2021;Kumari et al, 2021).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…With the higher infectious dose (10 4 PFU) or with IAV pre-infection, we observed widespread extensive viral antigen expression and involvement of the spinal cord. This suggests some dose dependence of virus spread in the CNS, as it was suspected in another study (Yinda et al, 2021), and an effect of prior damage in the respiratory tract (Clark et al, 2021). At the same time, we and others found virus in the olfactory epithelium and in neurons in the olfactory bulb (Carossino et al, 2021;Kumari et al, 2021).…”
Section: Resultssupporting
confidence: 79%
“…In the mice, the inflammatory processes were only mild and more pronounced in frontal regions like caudoputamen and the thalamus/hypothalamus region as well as the hippocampal area. Further vascular lesions apart from vasculitis/endotheliitis, like ischemic infarcts (Kantonen et al, 2020;Song et al, 2021) or microthrombi (Fabbri et al, 2020) that seem to be frequent in fatal human COVID-19 cases, are obviously not a regular feature in this mouse model, since only two studies reported occasional microthrombi in the brain (Yinda et al, 2021;Zheng et al, 2021). This could be due to the lack of endothelial cell infection in the brain of the mice, whereas it was seen in association with fresh ischemic infarcts in the brain of a COVID-19 patient (Meinhardt et al, 2021;Song et al, 2021).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…To assess the protective capacity of the VSV replicon we used transgenic K18-hACE2 C57BL/6 mice, which were previously shown to develop respiratory disease resembling severe COVID-19 [76]. Five mice each were immunized as before with VSVΔG-minispike-eGFP or VSVΔG-eGFP control and challenged intranasally with 10 4 TCID50 of SARS-CoV-2 Wetzlar, either following prime immunization or homologous boost immunization (Fig 7A).…”
Section: K18-hace2 Mice Are Protected From Sars-cov-2-induced Respiratory Disease After a Single Immunizationmentioning
confidence: 99%
“…Expression of hACE2 in mice via a transgene allows SARS-CoV-2 infection and provides mouse models that recapitulate aspects of COVID-19. In such models hACE2 is expressed under control of various promoters, including K18 (612), mACE2 (13, 14), HFH4 (15), or chicken β-actin (16). These mouse models all differ in various aspects including level of virus replication, disease manifestations and tissue tropisms (3), but do not provide a simple mechanism whereby genetically modified (GM) or knock-out mice can be exploited for SARS-CoV-2/COVID-19 research.…”
Section: Introductionmentioning
confidence: 99%